BTK: a two-faced effector in cancer and tumour suppression. Issue 11 (November 2018) - Rada, Miran; Barlev, Nickolai; Macip, Salvador
Abstract Many genes of the human genome display pleiotropic activity, playing an important role in two or more unrelated pathways. Surprisingly, some of these functions can even be antagonistic, often letting to divergent functional outcomes depending on microenviromental cues and tissue/cell type-dependent parameters. Lately, the Bruton's tyrosine kinase (BTK) has emerged as one of such pleiotropic genes, with opposing effects in cancer pathways. While it has long been considered oncogenic in the context of B cell malignancies, recent data shows that BTK can also act as a tumour suppressor in other cells, as an essential member of the p53 and p73 responses to damage. Since BTK inhibitors are already being used clinically, it is important to carefully review these new findings in order to fully understand the consequences of blocking BTK activity in all the cells of the organism.